Terahertz-wave decoding of femtosecond extreme-ultraviolet light pulses - Ilyakov, I.; Agarwal, N.; Deinert, J-C; Liu, J.; Yaroslavtsev, A.; Foglia, L.; Kurdi, G.; Mincigrucci, R.; Principi, Emiliano; Jakob, G.; Klaui, M.; Seifert, T. S.; et al. (Optica, 2022)
In recent years, femtosecond extreme-ultraviolet (XUV) and x-ray pulses from free-electron lasers have developed into important probes to monitor processes and dynamics in matter on femtosecond-time and angstrom-length scales. With the rapid progress of versatile ultrafast x-ray spectroscopy techniques and more sophisticated data analysis tools, accurate single-pulse information on the arrival time, duration, and shape of the probing x-ray and XUV pulses becomes essential. Here, we demonstrate that XUV pulses can be converted into terahertz electromagnetic pulses using a spintronic terahertz emitter. We observe that the duration, arrival time, and energy of each individual XUV pulse is encoded in the waveform of the associated terahertz pulses, and thus can be readily deduced from single-shot terahertz time-domain detection.
CRIS-Team Scopus Importer:2023-03-27